TRACE ELEMENT INCORPORATION INTO PYROPE-GROSSULAR SOLID SOLUTIONS: AN ATOMISTIC SIMULATION STUDY - van Westrenen W.; Blundy J.D.; Allan N.L.; Lucas B.R.; Lavrentiev M.Yu.; Purton J.A. (My University, 2003)
We have performed atomistic computer simulations on trace element incorporation into the divalent dodecahedral X-sites of pyrope (Py — Mg3Al2Si3O12) – grossular (Gr — Ca3Al2Si3O12) solid solutions. An ionic model and the Mott–Littleton two-region approach to defect energies were used to calculate the energetics of substitution by a range of divalent trace-elements and of charge-balanced substitution by trivalent ions in the static limit. Results are compared with experimental high-temperature, high-pressure garnet-melt trace element partitioning data obtained for the same garnet solid solution to refine our understanding of the factors controlling element partitioning into solid solutions. Defect energies (U def,f), relaxation (lattice strain) energies (U rel), and solution energies (U sol) were derived using two different approaches. One approach assumes the presence of one type of hybrid X-site with properties intermediate between pure Mg and Ca sites, and the other assumes discrete Mg and Ca X-sites, and thus two distinct cation sublattices. The hybrid model is shown to be inadequate, since it averages out local distortions in the garnet structure. The discrete model results suggest trace elements are more soluble in Py50Gy50 than in either end-member compound. Physically this is due to small changes in size of the X-sites and the removal of unfavourable interactions between third nearest neighbours of the same size. Surprisingly, depending on the local order, large trace element cations may substitute for Mg2+ and small trace elements for Ca2+ in Py50Gr50. These solubilities provide an explanation for the anomalous trace-element partitioning behaviour along the pyrope–grossular join observed experimentally.
Keywords: Element partitioning; Solid solutions; Garnet; Atomistic simulation